Safety analysis of a Class of Timed Automata Hybrid Systems - Megawati, Noorma Yulia (2009)
This paper investigates safety analysis of reachability of timed automata hybrid systems as an extension of safety analysis of linear system. By studying the initial and terminal sets, the safety analysis problems can be represented as geometric optimization problems which can be transformed into a linear programming. Solution of the optimization problem results in time interval of a safe and unsafe condition of linear systems. Safety analysis of linear systems is extended to safety analysis of timed automata hybrid systems which each mode is linear systems. Suppose given polyhedral sets of the initial state at mode i and terminal set mode i+1. The safety analysis is solved by determining the solution of the differential solution at mode i and the solution of the mode i at the discrete occurence. This solution the becomes the initial condition of the next mode i+1 and analysis by using the safety analysis.